Effects of breathing training on walking ability and quality of life in patients with multiple sclerosis: systematic review and meta-analysis of randomized controlled trials - Li, Cuiting; Kang, Jihe; Wang, Xiuli; Wang, Lulu; Li, Xiaoling (Frontiers in Immunology, 2025)
BackgroundIn recent years, an increasing number of studies have investigated the effects of breathing exercises on walking ability and quality of life in patients with multiple sclerosis (MS). However, the results of these studies are inconsistent. This study aims to explore the effects of breathing training on walking ability and quality of life in patients with MS through systematic review and Meta-analysis.MethodsPubMed, Web of Science, Embase and Cochrane English databases were systematically searched from inception to July 25 2025. Cochrane risk assessment tool and Physical Therapy Evidence database (PEDro) scale were used to evaluate the methodological quality of the included studies.ResultsIn total, 21 studies involving 881 patients were included. The 21 included studies demonstrated low risk of bias according to the Cochrane tool and high methodological quality (mean PEDro score = 6.24). The results revealed that, in terms of walking ability, breathing training significantly improved Berg Balance Scale (BBS) score (WMD, 3.25; 95%CI, 1.89 to 4.60, P < 0.00001, I2 = 58%). However, breathing training had no significant effect on the improvement of TUG (WMD, -0.96; 95% CI, - 2.12 to 0.20, P = 0.11, I2 = 0%) and 6WMT (WMD, 22.71; 95% CI, - 2.80 to 48.21, P = 0.08, I2 = 37%). In terms of quality of life, breathing training had a significant effect on measuring fatigue in patients with MS using FSS and MFIS assessments (SMD, -0.05; 95% CI, -0.76 to-0.24, P =0.0001, I2 = 57%)), but did not significantly improve the quality of life measured by SF-36 and MSQOL-54 (SMD, 0.15; 95%CI, -0.08 to 0.38, P= 0.19, I2 = 26%). In addition, breathing training had no significant effect on PSQI (WMD, -0.68; 95%CI, − 2.04 to 0.68, P= 0.33, I2 = 0%).ConclusionsBreathing training improves the balance function and alleviates fatigue symptoms in patients with MS, but there is no evidence to support its effects on functional mobility, overall quality of life and sleep quality. In the future, standardized breathing training programs should be established, and their long-term benefits for comprehensive functional rehabilitation of patients with MS should be further verified.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024600560.